2019
DOI: 10.3389/fonc.2018.00666
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Preoperative Multidetector-Row Computed Tomography for Axillary Lymph Nodes Metastasis in Patients With Breast Cancer

Abstract: Introduction: Axillary lymph nodes (ALN) status is an essential component in tumor staging and treatment planning for patients with breast cancer. The aim of present study was to evaluate the predictive value of preoperative multidetector-row computed tomography (MDCT) for ALN metastasis in breast cancer patients.Methods: A total of 148 cases underwent preoperative MDCT examination and ALN surgery were eligible for the study. Logistic regression analysis of MDCT variates was used to estimate independent predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 46 publications
(60 reference statements)
2
23
3
Order By: Relevance
“…These findings could be explained by the limited ability to obtain a complete visualization of the axilla on breast MRI without dedicated axillary protocol [ 26 ]. Prior studies have also demonstrated a high accuracy of MDCT in predicting axillary metastases in breast cancer [ 27 , 28 , 29 ]. Recently, Chen et al evaluated 148 breast cancer patients and found that the most important predictors of axillary lymph node metastasis on MDCT were cortical thickness > 3 mm and non-fatty hilum.…”
Section: Discussionmentioning
confidence: 99%
“…These findings could be explained by the limited ability to obtain a complete visualization of the axilla on breast MRI without dedicated axillary protocol [ 26 ]. Prior studies have also demonstrated a high accuracy of MDCT in predicting axillary metastases in breast cancer [ 27 , 28 , 29 ]. Recently, Chen et al evaluated 148 breast cancer patients and found that the most important predictors of axillary lymph node metastasis on MDCT were cortical thickness > 3 mm and non-fatty hilum.…”
Section: Discussionmentioning
confidence: 99%
“…However, these are invasive methods, with potential complications of arm pain, hematoma, seroma, lymphedema, and infection ( 6 ). Traditional imaging methods, including ultrasonography (US) ( 7 ), mammography ( 8 ), computed tomography (CT) ( 9 ), positron emission tomography/computed tomography (PET/CT) ( 10 ), and magnetic resonance imaging (MRI) ( 11 ), have all been used as noninvasive methods for evaluating the status of ALN in patients with breast cancer. However, some drawbacks to their use exist.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al. ( 7 ) have demonstrated in their cohort of 148 cases of patients with primary breast cancer undergoing axillary surgery that cortical thickness of more than 3 mm and a non-fatty hilum were independent predictors for metastases in the axillary nodes.…”
Section: Introductionmentioning
confidence: 99%